(untitled) (Research, Society and Development, 2022)
Depression affects all age groups and has been increasingly observed in children and adolescents. The symptoms most observed in this population are the drop in school performance, sadness and isolation, which intensify, impairing development and contributing to human disability. Thus, the present study aims to identify the possible causes for the occurrence of childhood depressive disorder, looking for influencing factors, both intrinsic and extrinsic to children and adolescents. For this, an integrative review was carried out, based on data available in PubMed, SciELO and Google Scholar, using the MeSH terms from PubMed: “Depressive disorder”, “Depressive symptoms”, “Children”, “Adolescents” in which 23 articles were selected. There are several risk factors that can lead children and adolescents to develop depressive disorder. The lack of affection from family members, living with a depressive parent, environmental stressors such as sexual and physical abuse and the loss of a loved one are some of these factors. Identifying childhood depressive syndrome is essential due to the need for interventions, use of treatment techniques and prevention of later problems, thus enabling a better quality of life for this future adult.